Botanicals: A promising approach for controlling cecal coccidiosis in poultry - Saeed, Zohaib; Alkheraije, Khalid A. (Frontiers in Veterinary Science, 2023)
Avian species have been always in problem due to coccidiosis. Among all types of coccidiosis cecal coccidiosis is the most dangerous for the avian species. Chicken and turkeys are commercial flocks, so their parasites have remained critical due to their economic importance. High mortalities and morbidities are observed due to cecal coccidiosis. The coccidiostat and coccidiocidal chemicals have been routinely added to feed and water to control of coccidiosis. After their ban on use by the EU, because of issues of resistance and public health, alternatives are being tried. vaccines are also being practiced but their efficacy and economics are the problems. Among the alternatives, botanicals are a promising choice. Botanicals contain multiple active compounds like phenolics, saponins, terpenes, sulfur compounds, etc. which can kill sporozoites and oocysts, and stop the replication of Eimeria. The most important function is that most of the botanical compounds are immunostimulants and antioxidants. Due to these properties, some commercial products have also been developed. Research is needed to estimate their pharmacological effects, mechanism of action, and methods of concentrated preparations to be used. In this review, an attempt has been made to summarize the plants having anticoccidial potential and the mode of action of different compounds has also been explained.